The Substantiation Of Spiritual And Moral Education As Per Tasawwufi Views Of Najmiddin Kubra - Umarovich, Khodjaniyazov Sardor (The journal of contemporary issues in business and government, 2021)
This article discusses issues such as humanity, human dignity, the quest for the truth, self-education, singing the love for Allah, calling to the path of truth in Najmiddin Kubra’s rubai. His views on the moral education are analyzed based on his treatises. The contextual analysis of some rubais is conducted based on the books compiled by the sufi scholar.